2020
DOI: 10.1016/j.healun.2019.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Impact of race on survival in pulmonary arterial hypertension: Results from the REVEAL registry

Abstract: BACKGROUND: Prior research has suggested that the prevalence and outcomes of pulmonary arterial hypertension (PAH) may vary by race or ethnicity. However, these studies have been limited by small sample size or methodological techniques relying on epidemiologic data. The purpose of this study is to evaluate the relationship between race/ethnicity and survival in a large U.S.-based prospective multicenter registry. METHODS: Patients in the Registry to Evaluate Early and Long-term PAH Disease Management (REVEAL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 33 publications
3
24
1
1
Order By: Relevance
“…Surprisingly, Asians/Pacific Islanders showed the greatest increase in mortality and total hospital charges of any race or ethnicity. Until the REVEAL registry, it was unclear whether different races or ethnicities had differing prognosis following the diagnosis of pulmonary hypertension; however, the authors of the REVEAL study concluded that race and ethnicity did not impact outcomes for patients with pulmonary hypertension [ 11 , 12 ]. In contrast, our study results show that Asians/Pacific Islanders are at a significantly higher risk than other races and ethnicities for mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, Asians/Pacific Islanders showed the greatest increase in mortality and total hospital charges of any race or ethnicity. Until the REVEAL registry, it was unclear whether different races or ethnicities had differing prognosis following the diagnosis of pulmonary hypertension; however, the authors of the REVEAL study concluded that race and ethnicity did not impact outcomes for patients with pulmonary hypertension [ 11 , 12 ]. In contrast, our study results show that Asians/Pacific Islanders are at a significantly higher risk than other races and ethnicities for mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our study results show that Asians/Pacific Islanders are at a significantly higher risk than other races and ethnicities for mortality. Also, Asian/Pacific Islander patients are more likely to have congenital heart disease-associated pulmonary hypertension, which would significantly increase their lifelong morbidity and mortality compared to patients first diagnosed with pulmonary hypertension in adulthood because those diagnosed in adulthood would likely have decreased lifetime survival and hospitalizations [ 11 ]. Genetic mutations in interaction with epigenetics and environmental factors, which may be present for Asians/Pacific Islanders, could also theoretically increase mortality in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in PAH has shown an association between worse outcomes and lower SES, so further investigation of geospatial determinants of health in PAH are worth consideration. 23,41 Socioeconomic Factors SDHs and SES have been identified as fundamental causes behind health disparities and racial differences in health. 32,58,63 These terms often incorporate factors that can alter health-related behaviors such as neighborhoods, income, education, wealth, occupation, health insurance coverage, and mar-ital status.…”
Section: Environmental and Geospatial Determinantsmentioning
confidence: 99%
“…Based on the RE-VEAL Registry, Black patients were less likely to be prescribed phosphodiesterase-5 inhibitors, and Hispanic patients were less likely to be prescribed ERA therapy. 23 Hispanic patients have been found to be treated with less PAH-specific medications in general. 18 Racial and ethnic minorities are less likely to have health insurance, and for minorities with PAH, the lack of health insurance may have the greatest impact on their quality of care and could play a part in prescribing patterns.…”
Section: Research In Pahmentioning
confidence: 99%
See 1 more Smart Citation